Severe Obstructive Sleep Apnea in an young Adult (Bangladesh Critical Care Journal, 2019)
Obstructive Sleep Apnea (OSA) is a serious common sleep disorder needs life long care. OSA is caused by recurrentupper airway obstruction due to increased upper airway collapsibility during sleep. It is highly associated with obesitywith several endocrine and metabolic diseases. Hypothyroidism may cause OSA, also linked with obesity. Obesity isalso a risk factor for hypertension.This paper is presenting a case of obstructive sleep apnea with obesity, hypertensionand hypothyroidism. A 35 years old male presented with the complaints of excessive day time sleepiness, loud snoring,fragmented sleep, apnea like attack, occasional morning headache. Whole night polysomnography was done anddiagnosed as severe obstructive sleep apnea. At therapeutic part of polysomnography, he was treated with BiPAP.BangladeshCrit Care J September 2019; 7(2): 109-110